Reception of J. W. Goethe’s work of the Weimar period in the Belarusian culture - Shmyk, Ekaterina A. (Human in the Socio-Cultural Dimension, 2021)
We consider the main stages and strategies of assimilation by Belarusian culture of J. W. Goethe’s work of the Weimar period. At each stage, we highlight the most representative events that influenced the development of the creative method of individual artists and Belarusian culture as a whole. We highlight the directions in which, at one time or another, there was an acquaintance with the heritage of J. W. Goethe and his reception in the Belarusian culture. We emphasise that the most fruitful in this process were the second half of the 20th century and the beginning of the 21st century, when the reception of J. W. Goethe’s work was carried out not only through literary translation, but also through theatrical, musical and visual art.
Keywords: Johann Wolfgang Goethe; German culture; Belarusian culture; German literature of the 18th century; dialogue of cultures; cultural contacts; literary translation; reception